2003
DOI: 10.1152/ajpregu.00657.2002
|View full text |Cite
|
Sign up to set email alerts
|

Countercurrent exchange in the renal medulla

Abstract: Pallone, Thomas L., Malcolm R. Turner, Auré lie Edwards, and Rex L. Jamison. Countercurrent exchange in the renal medulla. Am J Physiol Regul Integr Comp Physiol 284: R1153-R1175, 2003 10.1152/ ajpregu.00657.2002The microcirculation of the renal medulla traps NaCl and urea deposited to the interstitium by the loops of Henle and collecting ducts. Theories have predicted that countercurrent exchanger efficiency is favored by high permeability to solute. In contrast to the conceptualization of vasa recta as sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 139 publications
(257 reference statements)
2
102
0
2
Order By: Relevance
“…The DVR in the innermost 50% of the rat and kangaroo rat inner medulla also express little or no UT-B (15,49). However, functional studies in rats have shown that vasa recta from the deep papilla exhibit substantial urea Smooth muscle myosin heavy chain protein is expressed in renal arterioles (26,44), and its expression along the upper inner medullary DVR in the human kidney suggests that segments in the upper zone of the inner medulla have contraction and relaxation properties, as has been shown for DVR of the inner stripe of the outer medulla (32). The contractile properties of segments at deeper levels of the inner medulla, where smooth muscle myosin heavy chain protein expression is distributed more sparsely or is absent altogether, likely are different.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The DVR in the innermost 50% of the rat and kangaroo rat inner medulla also express little or no UT-B (15,49). However, functional studies in rats have shown that vasa recta from the deep papilla exhibit substantial urea Smooth muscle myosin heavy chain protein is expressed in renal arterioles (26,44), and its expression along the upper inner medullary DVR in the human kidney suggests that segments in the upper zone of the inner medulla have contraction and relaxation properties, as has been shown for DVR of the inner stripe of the outer medulla (32). The contractile properties of segments at deeper levels of the inner medulla, where smooth muscle myosin heavy chain protein expression is distributed more sparsely or is absent altogether, likely are different.…”
Section: Discussionmentioning
confidence: 90%
“…The inner stripe therefore consists of many vascular bundles running parallel to the corticomedullary axis, with each bundle carrying countercurrent flows. In both human and rat, the DVR feed into complex capillary networks that perfuse the interbundle region, with many capillaries feeding, in turn, to AVR (32). These DVR are lined by pericytes, which have a smooth muscle component whose contractile properties have the potential for regulating blood flow in both the inner stripe and the inner medulla (32).…”
mentioning
confidence: 99%
“…Thus, the medulla is in a hypoxic environment under a physiological state [1] . Such an arrangement is strategically necessary to maintain the corticomedullary osmotic gradient for fluid absorption and urine concentration [2] . To avoid energy deprivation in the low pO 2 regions, an array of hormones, autocoids, and vasoactive substances, mostly synthesized in the medulla, including medullipin, prostaglandins, endothelins, nitric oxide, angiotensin II, kinins, and adenosine are required [1,3] .…”
Section: Kidneys Are Vulnerable To Inflammatory Insultsmentioning
confidence: 99%
“…In mice, descending limbs of short loops migrate within vascular bundles and lie adjacent to peripheral vasa recta. DVR endothelia and red blood cells (RBCs) express aquaporin (AQP)-1 water channels and urea transporter (UT)-B so that their equilibration occurs by a combination of solute influx and solute-free water removal (6,7). DVR and AVR are not simply diffusive countercurrent exchangers.…”
mentioning
confidence: 99%